Sistem Penunjang Keputusan Untuk Menentukan Santri Berprestasi Menggunakan Metode SAW (Studi Kasus : Pondok Pesantren Al-Ma’ruf Lampung) - Catur Tyas Surya Wigatil; Sri Ipnuwati; Khozainuz Zuhri (Jurnal Teknologi dan Informatika (JEDA), 2022)
The Darussalam Islamic Boarding School Sidorejo, East Lampung annually issues the predicate of outstanding students which is calculated based on attitude or personality values, report cards, extracurricular values, and absent grades. To determine the students who are entitled to the best grades, the boarding school must calculate the value of all student data every year. Therefore, the authors propose a web-based decision support system for outstanding students using the SAW (Simple Additive Weighting) method. The SAW (Simple Additive Weighting) method is used to make it easier for teachers and homeroom teachers to determine outstanding students. This system is applied to support the decisions of outstanding students who have previously used conventional systems or manually to digital-based systems and can display in detail and can be proven by the system.